Інформаційні технології в діагностиці процесів дефектоутворення мікро- та наноелектронних структур - Пятайкіна, М. І.; Стрілкова, Т. О. (ХНУРЕ, 2025)
The paper presents a method for diagnosing defect formation processes in micro- and nanostructures based on information technologies. The entropy analysis method was used. Statistical parameter calculations of technological images were performed. Mathematical modeling of a defect recognition algorithm for various spatial dimensions is presented.
Keywords: дефектоутворення; діагностика процесів дефектоутворення